Volume 3B: Biomedical and Biotechnology Engineering 2013
DOI: 10.1115/imece2013-65406
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction in Corneal Epithelial Cells

Abstract: Mechanical properties of the cornea can be affected by diseases such as keratoconus. In keratoconus, a decrease in both thickness and rigidity of the cornea is observed. It is currently not clear whether and how changes in mechanical properties of the cornea are associated with corneal epithelial cell behavior. In the present study, polyacrylamide (PAA) gels with different elastic moduli have been prepared and human corneal epithelial cells (HCECs) have been cultured on them. To investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…This phenomenon has also been observed in PLLA/dioxane/water ternary system by He et al (44). Pores near the wall of scaffolding molds were typically smaller than those in the middle, because the cooling rate is higher near the wall (42).…”
Section: Effect Of Cooling Ratesupporting
confidence: 69%
See 2 more Smart Citations
“…This phenomenon has also been observed in PLLA/dioxane/water ternary system by He et al (44). Pores near the wall of scaffolding molds were typically smaller than those in the middle, because the cooling rate is higher near the wall (42).…”
Section: Effect Of Cooling Ratesupporting
confidence: 69%
“…This phenomenon might connect to the incomplete microstructure formation at a low concentration (43). Sara et al also found that higher PLLA concentrations increased the thickness of pore walls and could also uniform the pore size (42).…”
Section: Effect Of Polymer Concentrationmentioning
confidence: 97%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The most recent papers focused on the preparation of BTA by particle leaching, gas foaming technique, [15] electrospinning, [16][17][18] layer by layer casting technique, [19] rapid prototyping, [20,21] thermal induced phase separation, [22] centrifugation freeze drying, [23,24] triply periodic minimal surfaces (TPMS), [25] freeze casting. [26][27][28][29][30] Most of the methods presented in the scientific literature are based on the dissolution of the polymeric phase in a specific solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The ideal scaffolds should mechanically support the newly formed tissues as well as deliver inductive molecules or cells to the repair site and provide cues to control the structure and function of the new tissue . To fulfill this role, three‐dimensional porous architectures have been fabricated using various techniques, such as porogen leaching, phase separation, solvent casting and freeze‐drying …”
Section: Introductionmentioning
confidence: 99%